Pengaruh Iklim Organisasi dan Beban Kerja Terhadap Komitmen Organisasi Perawat dengan Motivasi Kerja Sebagai Variabel Intervening - Novita Widyawaty; Supriyantoro Supriyantoro; Hasyim Hasyim (Jurnal Health Sains, 2022)
Hospitals need nurses with organizational commitment and high work motivation because nurses will contribute highly in providing quality and professional services to patients. Thus, hospital management needs to know what factors will support the formation of organizational commitment and work motivation of nurses. To analyze the effect of organizational climate and workload on organizational commitment of inpatient nurses through work motivation as an intervening variable. This research is a quantitative descriptive survey using SPSS software for data processing. Of the total 53 questionnaires filled in, 49.1% of nurses had worked for more than 5 years. Currently, nurses consider the organizational climate to be quite conducive with a moderate workload. Based on statistical measurements, currently inpatient nurses have moderate organizational commitment and high motivation to work. Organizational climate and workload affect the organizational commitment of inpatient nurses through work motivation as an intervening variable. The findings in this study can be used as input for hospital management to develop strategies to increase organizational commitment and work motivation of nurses.